2013
DOI: 10.5455/jeos.20130220105759
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis B virus infections among health care workers at the Bulle Hora Woreda Governmental Health Institutions, Southern Oromia, Ethiopia

Abstract: Background: Health care workers (HCWs) are at a great risk of occupational exposure with blood borne pathogens like Hepatitis B virus. The risk of occupational exposure to such infection has been the concerns of HCWs for years. However, there were scarcity of information on prevalence and risk factors of Hepatitis B virus infection in the study area. Objective: This study was aimed to determine the seroprevalence and associated risk factors of Hepatitis B virus infections among Health care workers. Method: A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 16 publications
8
33
1
1
Order By: Relevance
“…Several studies have shown that HCW's are at higher risk of having HBV infection as compared to the general population 15 16 which is very near to the response to the same question i.e. 100% in our study (Figure 1).…”
Section: Discussionsupporting
confidence: 56%
“…Several studies have shown that HCW's are at higher risk of having HBV infection as compared to the general population 15 16 which is very near to the response to the same question i.e. 100% in our study (Figure 1).…”
Section: Discussionsupporting
confidence: 56%
“…2b). The HBsAg was also reported among various segments of the society such as healthcare professionals (7.3–9.0%) [29, 30], medical waste handlers (6.0–6.3%) [31, 32], outpatient and inpatient department attendants (4.7–7.4%) [33, 34], street dwellers (10.9%) [35], pregnant women (3.0–7.3%) [36–40], diabetic patients (3.7%) [41], HIV VCT centres clients (5.7%) [10, 42] and commercial sex workers (6.0%) [43] (Fig. 2c).…”
Section: Resultsmentioning
confidence: 99%
“…The HBsAg prevalence was hyperendemic among healthcare professionals [29] and medical waste handlers [30] in particular might be associated with occupational risk exposures since they deal with all sorts of the infected samples with no HBV vaccination, which is the simplest protection and standard practice elsewhere. A recent study showed that although knowledge about availability of HBV vaccine was 62% among healthcare workers, fully vaccinated professionals were only 5.4% [76].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted among HCWs of Bulle Hora Woreda, Southern Oromia, revealed that only 2 (1.2%) of the HCWs were vaccinated [14], and a study in St. Paul’s and Zewditu hospital, Addis Ababa showed 9 (3.5%) had history of vaccination even though none of them were fully vaccinated [15]. A study in Harar also showed only 15 (4.7%) of the respondents were fully vaccinated against HBV [16].…”
Section: Discussionmentioning
confidence: 99%